1999
DOI: 10.1111/j.1365-2621.1999.tb15898.x
|View full text |Cite
|
Sign up to set email alerts
|

Production of Polysaccharide by Rahnella aquatilis with Whey Feedstock

Abstract: The rates were monitored on biomass increase, polysaccharide production and viscosity development of whey broth and a control synthetic broth during fermentation by Rahnella aquatilis and organic acids, lactose, peptides and free amino acids were measured. Growth curves were similar and characterized by maximum specific growth rates of 0.61 h Ϫ1 for whey and 0.63 h Ϫ1 for synthetic medium. The yields of polysaccharide were 0.59 g/g lactose for the synthetic medium and 0.56 for whey. Small peptides (Ͻ4,000 Da) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2003
2003
2020
2020

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 21 publications
1
8
1
Order By: Relevance
“…The differences observed between nonwashed and washed cells seemed to mainly involve the peptide and lipid components suggesting that the contents of these substances differ between cells and EPS. The washed cells appeared to display larger percentages of peptide, which may indicate an EPS with relatively high percentage of polysaccharide and lipid‐like substances compared with the bacterial cell, in line with previous reports 26 …”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The differences observed between nonwashed and washed cells seemed to mainly involve the peptide and lipid components suggesting that the contents of these substances differ between cells and EPS. The washed cells appeared to display larger percentages of peptide, which may indicate an EPS with relatively high percentage of polysaccharide and lipid‐like substances compared with the bacterial cell, in line with previous reports 26 …”
Section: Resultssupporting
confidence: 91%
“…This river isolate was included as we observed that it produced very large quantities of EPS that was clearly visible by eye on culture plates as well as in liquid culture. This species is also known to have production of organic acids as well as extracellular polysaccharides of interest to industrial applications 26–28 . In cryo‐SEM images, the secreted EPS is clearly observed as a layer in which the cells are dispersed (Figure 1A,B).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…protease such as pronase E, proteinase K or flavourzyme) or sequential combination of both, and removal by centrifugation followed by EPS concentration by ethanol precipitation (Dinic et al, 2018;Marshall et al, 2001;Wang, Zhao, Yang, Zhao, & Yang, 2015;Yang et al, 2018). Other protein precipitating agents (Greenberg & Shipe, 1979) such as 12 M HCl (Enikeev, 2012;Khanal & Lucey, 2017) 5-sulfosalycilic acid (SSA) (Pintado, Pintado, & F. Malcata, 1999a;Pintado, Pintado, & Malcata, 1999b) or ammonium sulphate (Peng, Han, Liu, & Zhou, 2016), have also been successfully introduced. After the EPS precipitation, the last step of EPS purification generally includes the resuspension of resulting material in deionized water and its dialysis against water for 1 to 7d at 4°C to remove low-molecular-mass contaminating carbohydrates that may be present in the material, and finally the resulting EPS is lyophilized (Abid et al, 2018;Benit & Roslin, 2018;London et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Rahnella might improve the supply of plants with nutrients like phosphate (Kim et al, 1997) and it is able to fix nitrogen (Heulin et al, 1994). The polysaccharides levan and lactan produced by different strains of Rahnella have interesting properties for industrial processes (Kim et al, 2003;Matsuyama et al, 1999;Pintado et al, 1999;Seo et al, 2002). The high uranium(VI) resistance of Rahnella and its ability to bind this toxic heavy metal is currently intensively investigated and its potential for bioremediation is studied (Beazley et al, 2007;Geissler et al, 2009;Martinez et al, 2007).…”
mentioning
confidence: 99%